Protocol: Assessing the outcomes and impact of professional doctorate programmes in health and social care on the individual, their profession, their employing organisation and wider society: A comprehensive systematic review - Hazel M. Chapman; Robert McSherry; Josette Bettany‐Saltikov; Mridula Mohan; Debbie Spencer (Campbell Systematic Reviews)
Abstract This is the protocol for a Campbell systematic review. This review's objectives are to find out (in relation to health and/or social care): (1) What is known about the outcomes and impact of completing (or not completing) a professional doctorate in health and/or social care on the individual professional? (2) What is known about the outcome and impact of completing (or not completing) a professional doctorate in health and/or social care on the employing organisation? (3) What is known about the outcome and impact of completing (or not completing) a professional doctorate in health and/or social care on the profession? (4) What is known about the outcome and impact of completing (or not completing) a professional doctorate in health and/or social care on service users and the wider society? (5) How do we use the findings from this review to inform educators, higher education institutions, professionals, investors in employing organisations and policymakers? (6) What further research will be needed to answer any knowledge gaps or recommendations? (7) Where possible, we will identify and report on any demographic data and discuss their relevance to the impact and outcomes from professional doctorates.